Correlation Abundance Networks for Analyzing Biological Interactions during Cyanobacterial Blooms - Alvarez Dalinger, Florencia Soledad (2024)
Introduction: Blooms of cyanobacteria are becoming increasingly common, and understanding their dynamics can be crucial for proposing appropriate management strategies. While physical and chemical parameters influencing blooms have been widely studied, less attention has been paid to the susceptibility of biological communities. Objective: The purpose of this study was to analyze phytoplankton abundance networks during cyanobacterial blooms at different intensity levels and how they interact and/or affect the phytoplankton community. Methods: We used 22 samplings conducted in El Limón reservoir located in northern Argentina, known for recurrent cyanobacterial blooms. Each sampling was classified into four levels based on cyanobacteria abundance (cells/ml): Level 1 (10 000-30 000); Level 2 (30 000-50 000); Level 3 (50 000-100 000); and Level 4 (> 100 000). For each level, abundance correlation networks were constructed considering all species. Results: A pattern of decreasing statistically significant abundance correlations was observed as bloom intensity increased: 219 correlations at Level 1; 144 at Level 2; 80 at Level 3, and only 33 at Level 4. Blooming cyanobacteria showed few correlations with other species at all levels, indicating a certain independence from the community. An increase in bloom intensity appears to disconnect the phytoplankton abundance correlation network. Conclusion: The analysis of abundance correlation networks should be a valuable tool for understanding the dynamics and development of cyanobacterial blooms, as well as identifying key species in this process.